Closing the circle. (Economist, 2014)
The article discusses the protests that reportedly took place in front of computer company Google Inc.'s offices in Berlin, Germany in opposition to the firm's alleged support for the iWright novel writing computer software program. According to the article, many Germans have an aversion (Googlephobia) to Google Inc. due to the belief that the firm ingests intellectual property, personal data, and democracy. German Social Democratic Party member Sigmar Gabriel is assessed.